10=3l-1

Simple and best practice solution for 10=3l-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10=3l-1 equation:


Simplifying
10 = 3l + -1

Reorder the terms:
10 = -1 + 3l

Solving
10 = -1 + 3l

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Add '-3l' to each side of the equation.
10 + -3l = -1 + 3l + -3l

Combine like terms: 3l + -3l = 0
10 + -3l = -1 + 0
10 + -3l = -1

Add '-10' to each side of the equation.
10 + -10 + -3l = -1 + -10

Combine like terms: 10 + -10 = 0
0 + -3l = -1 + -10
-3l = -1 + -10

Combine like terms: -1 + -10 = -11
-3l = -11

Divide each side by '-3'.
l = 3.666666667

Simplifying
l = 3.666666667

See similar equations:

| a^2=b^2 | | r^2*pi*80=12000 | | 25/50= | | 20/50= | | x+20/53*3= | | 10X=3750-10X | | 10=3750-10X/X | | x^3-4x^2-105=0 | | x^2-4X-105=0 | | h=1+x-x^2/40 | | x^3-4x-105=0 | | -7k=-91 | | x^3-4x+105=0 | | v/2=-9 | | b/6=5/6 | | 6/6=-5/6 | | p/3=-10 | | x/10=-7 | | 26=80/x^2 | | y^5=32 | | 3=y-4x | | 5(2x+7)-4=3-2(x+1) | | 3x+9=64-5x | | 10p^2+6p-5=0 | | (1/x^2)+x^2=62 | | 1/x^2+x^2=62 | | 2/5+120=x | | 13x+4=5x+20 | | 6x^2-10x-21=-5 | | 2x^2-x-52=3 | | 3v^2+11v+11=3 | | -3n^2-9n-6=0 |

Equations solver categories